Metabolic Effects of a Succinic Acid<Based Substrate Antihypoxant - B. N. Shakh; V. N. Lapshin; A. G. Kyrnyshev; D. B. Smirnov; N. R. Kravchenko-Berezhnaya (Общая реаниматология)
The paper discusses promises for clinical use of substrate antihypoxants.Objective: to investigate the efficacy of succinate containing  substrate  antihypoxants  on  systemic  oxygen  consumption,  blood  buffer  capacity,  and  changes  in  the  mixed venous blood level of lactate when they are used in gravely sick patients and victims with marked metabolic posthypoxic disorders.Subjects and methods. The trial enrolled 30 patients and victims who had sustained an episode of severe hypoxia of mixed genesis, the severity of which was evaluated by the APACHE II scale and amounted to 23 to 30 scores with a 46 to 70.3% risk of death. The standard infusion program in this group involved the succinate-containing drug 1.5% reamberin solution  in  a  total  dose  of  800  ml.  A  comparison  group  included  15  patients  who  had  undergone  emergency  extensive surgery for abdominal diseases. 400 ml of 10% glucose solution was used as an infusion medium. Oxygen consumption (VO2ml/min) and carbon dioxide production (VCO2ml/min) were measured before infusion and monitored for 2 hours. Arterial blood gases and acid-base balance (ABB) parameters and mixed venous blood lactate levels were examined. Measurements were made before and 30 minutes after the infusion of reamberin or glucose solution.Results. Infusion of 1.5% reamberin solution was followed by a significant increase in minute oxygen consumption from 281.5±21.2 to 310.4±24.4 ml/min. CO2 production declined (on average, from 223.3±6.5 to 206.5±7.59 ml/min). During infusion of 10% glucose solution, all the patients of the comparison group showed a rise in oxygen consumption from 303.6±33.86 to 443.13±32.1 ml/min, i.e. about 1.5-fold. VCO2 changed similarly. The intravenous infusion of 800 ml of 1.5% reamberin solution raised arterial blood buffer capacity, which was reflected by changes in pH, BE, and HCO3. There was a clear trend for lactate values to drop in the mixed venous blood. The intravenous injection of 400 ml of 10% glucose solution caused no significant changes in major ABB indicators, which reinforced the statement that there is a difference in the metabolism of these substrates.Conclusion. The succinate-containing drugs are able to compensate for metabolic acidosis. Their use is followed by increased oxygen consumption  and  activated  aerobic  oxidation  processes.  The  basis  of  their  antihypoxant  properties  was  thought  to  be recovered intracellular aerobic metabolic processes due to corrected intracellular metabolic acidosis and increased blood  buffer capacity.